Work, telework, and mental health during COVID-19 Trabajo, teletrabajo y salud mental en el contexto COVID-19 - Gallegos de San Vicente, Miguel Omar (2023)
This review addresses the impact of the COVID-19 pandemic on workers’ mental health, in particular, teleworking conditions. Our analysis is based on documents from several international organizations and specialized scientific publications. The retrieved information reveals that the pandemic has had a significant effect on the mental health of frontline workers and employees who had to migrate to a virtual environ-ment without prior warning. However, a positive aspect is reflected in the development of several remote mental health care devices implemented to protect vulnerable population, frontline worke-rs, and the general population. Finally, this paper underscores the importance of developing public policies for protecting workers’ mental health.